PENGARUH RASIO LIKUIDITAS, PROFITABILITAS, DAN AKTIVITAS TERHADAP HARGA SAHAM DI MASA PANDEMI COVID 19 PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI - Vendola Yolanda; Endang Etty Merawati; Mira Munira (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2023)
This study aims to examine the effect of Liquidity Ratio, Probability Ratio, and Activity Ratio partially on stock price in food and beverage subsector manufacturing companies during the Covid-19 pandemic. The independent variables used in this study are Current Ratio (CR), Return On Equity (ROE), and Total Asset Turn Over (TATO). The dependent variable in this study is the stock price. The population in this study are food and beverage sector companies listed on the Indonelsia Stock Exchange for the period 2020-2021 by determining the sample using purposive sampling, so that 10 companies meet the criteria. The data source for this research is quarterly financial reports taken from the official website of the Indonelsia Stock Exhange www.idx.co.id and then analyzed using SPSS Velrsion 26. The results of this study indicate that partially Return On Equity (ROE) and Total Asset Turn Over (TATO) variables have a significant effect on stock price, while Current Ratio (CR) variable has no significant effect on stock price.